Revelation of Immune Memory at the First Stage of Antigen-Specific Cell Response after Second Introduction of the Live Plague Vaccine - B. V. Karalnik; P. N. Deryabin; T. G. Denisova; T. S. Ponomareva; G. B. Zunussova; S. B. Zakaryan; R. B. Muchamedyarova (Эпидемиология и вакцинопрофилактика)
Background. The study of immune memory is necessary to evaluate the effectiveness of immunization against infection, including plague and to make a choice of vaccination scheme.Goals. The goal is to study the possible role of immune memory in the early stage of the antigen-specific response – the formation of cells with receptors for capsular (F1) and lipopolysaccharide (LPS) antigens of plague live EV vaccine.Methodology. Volunteers vaccinated with live plague vaccine EV for the first time (6 persons – group 1) and again (6 persons – group 2) were examined. In the mononuclear fraction of the blood of volunteers the cells binding antigens F1 and LPS Y. pestis (CBA) were determined.Results. In the volunteers group 2, the content of CBA at 2 days after vaccination was higher than in group 1. Between the 5th day and the end of the CBA detection, their content in group 2 decreased, and in group 1, it increased, but remained significantly less than in group 2 two days after immunization.Сonclusions. It is shown that the previous vaccination accelerates the first stage of the antigen-specific human response to second vaccination against plague. This reflects the role of immune memory in the formation of this stage of the immune response at vaccination against plague.